Du centre à la droite radicale : concurrence politique, tergiversations programmatiques et repositionnement idéologique du Parti colorado en Uruguay (1950-2015) - Damien Larrouqué (Les Cahiers ALHIM)
This article examines from a historical perspective the process of political, programmatic and ideological mutation of the Colorado Party in Uruguay throughout the second half of the 20th century. Historically located in the center of the political spectrum, the Colorado Party has dominated Uruguayan politics for over a century. However, apart from the electoral strengthening of its historical and conservative rival (the National Party), the Colorado Party has been seriously challenged by the left since the foundation of the Broad Front in 1971. For one decade, this catch all party has been relegated to the third electoral position. Consequently, its new leader has chosen to corner a political space unoccupied for a long-time and precisely situated in the farright. Our main ambition is to explain the reasons of the electoral decay of the Colorado Party and to understand the ins and outs of its contemporary ideological repositioning.